ASYMPTOTIC STABILITY AND BOUNDEDNESS OF SOLUTION OF 3rd ORDER NONLINEAR DIFFERENTIAL EQUATION - ABID MOHAMMED, SIZAR (Journal of Duhok University, 2019)
In this paper by using the Lyapunov function we investigate the asymptotical stability and boundedness of solution or 3rd order nonlinear differential equation. By using Lyapunov direct method to determine the asymptotic stability and bounded of solution for nonlinear differential equation by using a suitable Lyapunov function.